Gender Analysis Pathway Pada Pengembangan Pariwisata Di Desa Wisata Nongkosawit Kota Semarang: Gender Pathway Analysis On Tourism Development In Nongkosawit Tourism Village, Semarang City - Hidayati, Rizki; Larasati S, Endang; Yuniningsih, Tri (PERSPEKTIF, 2024)
The tourism sector, particularly the development of tourist villages, can be an effective tool to promote gender equality. However, women often face disparities, especially in economic opportunities and decision-making. This issue highlights the importance of this research, which aims to analyze the implementation of gender mainstreaming in tourism development in Nongkosawit Tourism Village, Semarang City. The study uses a qualitative descriptive method with the gender analysis pathway technique, focusing on four aspects: access, participation, control, and benefits. The snowball technique was used to determine the informants, with the head of the local tourism awareness group (Pokdarwis) as the key informant. The results show that Nongkosawit has begun to implement gender mainstreaming principles, particularly in terms of access and benefits. However, participation and control remain suboptimal due to the limited understanding of gender-responsive concepts in the community. As a result, women's participation in decision-making and leadership is still low, and they face difficulties accessing capital to start tourism-related businesses. The study recommends increasing gender-related education and fostering partnerships between the government, local organizations, and communities to ensure inclusive and sustainable tourism development that benefits both women and the local community.